The traits of the plant growth promoting acetic acid bacterium, Nguyenibacter vanlangensis - Vu, Huong Thi Lan; Bui, Van Thi Thu; Bui, Uyen Thi Tu; Yukphan, Pattaraporn; Malimas, Sukunphat; Kieu, Nam Phuong; Muramatsu, Yuki; Tanasupawat, Somboon; Le, Binh Thanh; Yamada, Yuzo; Tanaka, Naoto (Vietnam Journal of Science and Technology, 2019)
Two Nguyenibacter vanlangensis strains TN01LGIT and VTH-AC01 isolated by an enrichment approach using nitrogen free LGI medium from Asian rice isolation sources are expected as an additional PGPB within the Acetobacteraceae family. In this study, nitrogen fixing capability of the two N. vanlangensis strains was confirmed through nitrogenase activity’s detection by acetylene reduction analysis...